2014
DOI: 10.1590/1982-0194201400028
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida antes e após a cirurgia bariátrica

Abstract: Objective: Knowing the quality of life of obese patients before and after bariatric surgery. Methods: A cross-sectional and prospective study that included 16 obese patients who underwent bariatric surgery. The survey instrument was the Whoqol-bref translated and validated for the Portuguese language. Data were collected before and after the bariatric surgery. The SPSS 19.0 was used for data analysis with application of the McNemar's test for related samples, considering p<0.05 significant. Results: Before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
8
0
6
Order By: Relevance
“…A study that assessed QoL of patients before and after bariatric surgery in the Brazilian public health system showed that after surgery, 82.2% of patients considered their quality of life as being good or very good, which contrasted the 40% of patients who expressed the same opinion during the preoperative period (15) . These fi ndings confi rm that an improved quality of life is fundamental for the success of bariatric surgery, which often transforms the lives of obese individuals (16) .…”
Section: Discussionmentioning
confidence: 77%
“…A study that assessed QoL of patients before and after bariatric surgery in the Brazilian public health system showed that after surgery, 82.2% of patients considered their quality of life as being good or very good, which contrasted the 40% of patients who expressed the same opinion during the preoperative period (15) . These fi ndings confi rm that an improved quality of life is fundamental for the success of bariatric surgery, which often transforms the lives of obese individuals (16) .…”
Section: Discussionmentioning
confidence: 77%
“…Esse instrumento avalia a perda de excesso de peso, a melhora das comorbidades e cinco aspectos referentes à qualidade de vida, entre eles: autoestima, disposição para atividades físicas, desempenho no trabalho, interação social e prática de atividade sexual. 12,13 Nesse sentido, tendo em vista que a cirurgia bariátrica é considerada um tratamento eficaz no controle de peso, no prognóstico positivo das comorbidades associadas e também da qualidade de vida de pacientes obesos, o presente estudo teve como objetivo avaliar o perfil nutricional e a qualidade de vida de indivíduos submetidos a cirurgia bariátrica em um hospital público da cidade de Goiânia-GO, caracterizando o perfil antropométrico, hábitos de vida no período pósoperatório e alterações na percepção da qualidade de vida.…”
Section: Introductionunclassified
“…Excess body fat can give rise to cardiovascular, renal and digestive diseases, diabetes mellitus, kidney and orthopedic diseases and reduce motor performance. 8 Decreased motor performance is evident with age progression and may be linked to the ageing process, degenerative pathologies, lifestyle or a combination of these factors. The ability to perform known functions such as the activities of daily living (ADLs) and the instrumental activities of daily living (IADLs) requires motor abilities related to strength, flexibility, aerobic capacity and balance; and the cognitive actions are related to executive functions, attention and memory.…”
Section: Introductionmentioning
confidence: 99%